Populism in the 2017 Jakarta Gubernatorial Election - Abdul Hamid (Journal of Governance, 2019)
The 2017 Jakarta Gubernatorial Election was one of the most competitive local elections in Indonesia. This election clearly used religious and ethnic populism strategy that divided Jakarta citizens into two groups: A Muslim Governor’s supporters Vs. Incumbent`s supporters. The root of the Muslim governor’s supporters was the rejection of some Islamic organizations against the rise of Chinese-Christian Incumbent Governor – Basuki Tjahaja Purnama or “Ahok”. This sentiment found a momentum when Ahok was accused of blasphemy against Islam that provoked Muslims furious. Moreover, Anies Baswedan became a successful candidate utilizing the sentiments and used mosques to echo the resistance against non- muslim Governor candidate.